Experential Learning (Pembelajaran Berbasis Mengalami) - Anggreni Anggreni (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Learning is the process of changing individual behavior as a result of interaction with the environment. It is a system consisting of components  interacting with ano another to achieve the goals of teaching that has already been predetermined. One of the learning model that is often used in learning theory is experiential learning (experience-based) learning. Experiential learning was first introduced by David A. Kolb. Experiential learning is an effort to achieve the goals based on experiences that are constantly changing in order to improve the effectiveness of the learning outcomes themselves. The purpose of this experiential learning model is to influence students in three ways, namely: (a) changing student cognitive structure, (b) changing student attitudes, (c) extending existing student skills. Learning procedure in the experiential learning consists of 4 stages: (a) concrete experience, (b) reflection observation, (c) conceptualization / reflection observation, (d) active experimentation. David Kolb divides one's learning style into four categories: diverger, assimilator, converter and accomodator. Experiential learning is organized and implemented by focusing more on the things that are owned by students. This principle also relates to experience in performing tasks in the usual ways of learning undertaken by students.Keywords: Learning, experiment learning, learning outcomes